Arterial pulse waveform and PWV - Chew, Jek HuI (2018)
Cardiovascular diseases has been on a rising trend in recent years and there are many risk factors including diet and age. A person’s age and the stiffness of his arterial walls are two of the most established cardiovascular risk factors. Further test are being done in this Final Year Project (FYP) to establish the link between age and stiffness of arterial wall. The main objective of this FYP is to confirm which Pressure Independent Index (PIIs) is the best for predicting the PWV values of a person. In addition, the use of Matlab for the calculation of the PIIs has also been tested out to backtest the PII values that have been calculated. Out of the 5 formulated PIIs, PII 5 is found to be the best indicator for estimating PWV values. This is because it has only an estimate error of 2.16% compared to 3.46% for ratio 4, 4.51% for ratio 3, 4.4% for ratio 2 and 4% for ratio 1. This is despite PII 2 being found to have the strongest correlation with age and PWV. This could be due to the fact that having a common geometrical area for comparison would ensure a more consistent estimated PWV value. Having found PII 2 to have the least error in terms of predicting the PWV value, its inclusion in the Stroke Index can be further investigated.